In the land of Iara, Iracema and Macyrajara, what health practices will I offer? Analysis of the trajectories and perspectives of health policies for indigenous peoples in Brazil (Research, Society and Development, 2021)
There are indigenous people on the North and South American continents who dwelled there before the Portuguese, Spanish, French, English, or Dutch invasions. With the European colonization, much of the indigenous population was enslaved, Christianized, and decimated almost completely. Presently, besides everyday challenges, such as rights and access to the homeland, agribusiness clashes, and other threats, there is a precariousness in the management and provision of healthcare provided to the Amerindians. This paper aims to draw a timeline on the state of health of Brazilian indigenous people, identifying its subjects, assessing its contexts, and discussing the legal milestones. Indigenous health policies hold (or at least should hold) a central position in the provision of healthcare to the indigenous population wherein they offer integral, universal, and equanimous healthcare services. Despite this, the urge to recognize some fragility restrains the management and provision of the health policies for the indigenous people.